International Coordinator Survey Results on the Outpatient Management of Patients with the Heartware® Ventricular Assist System. Issue 11 (November 2016) - Schlöglhofer, Thomas; Robson, Desiree; Bancroft, Jayne; Sørensen, Gro; Kaufmann, Friedrich; Sweet, Leslie; Wrightson, Neil
Purpose: While the HeartWare® Ventricular Assist System (HVAS) is a successful therapy for end-stage heart failure, outpatient management methods can vary significantly and require further investigation. Methods: A survey to assess the long-term HVAS patient management and monitoring strategies was completed by 36 international heart centers that currently have over 1, 450 patients on VAD support either at home or in the hospital. Multiple choice questions examined VAD program characteristics, anticoagulation management, driveline exit-site dressing and showering recommendations, blood pressure and pump parameter monitoring, and patient discharge protocols. Results: Outpatient international normalized ratio (INR) was most frequently measured every 3–4 days (28.6%), and the most frequent schedule for changing driveline exit site dressings was 3 times per week (30.6%). Only 25.7% of centers required their patients to measure blood pressure at home. A subgroup analysis was performed to assess the influence of center experience and larger centers generally had more frequent monitoring compared to smaller centers. Conclusions: This survey showed specific differences in outpatient management strategies that were previously unreported. However, further studies with correlations to patient outcomes are necessary to determine optimal patient management recommendations.